Prevención de la depresión unipolar en España: realidad y futuro (2008)
Unipolar depression is one of the most common illnesses in western society. There are multiple risk factors and many of them are preventable. However, planning of primary prevention of depression is not taken very seriously in Spain. We conclude that there are various political and academic reasons for this situation. They both can be overcome if we take prevention of depression more seriously. Keywords: Unipolar depression, Primary prevention, Universal prevention, Preventive intervention programs.